Evaluation of stocking density effects in closed wet transport on juvenile Asian Redtail catfish (Mystus nemurus) - Aldi Huda Verdian; Adni Oktaviana; Kevin Dony Kesuma; Nurul Fatimah; Irzal Effendi; Iis Diatin; Tatag Budiardi (Universitas Malikussaleh, 2026)
This study aims to evaluate the effect of stocking density variation on the survival rate of Asian Redtail catfish juveniles (Mystus nemurus) in a closed wet transportation system for 12 hours and post-transportation maintenance for 4 days. The method used a completely randomized design with three density treatments: 83, 167, and 250 fish per liter, each replicated three times. The results showed that a stocking density of 167 fish per liter provided the best survival rate, reaching 100% at the end of transportation and 95,45% after post-transportation maintenance. At the highest density of 250 fish per liter, a significant decline in survival to 64,39% was observed, accompanied by decreased water quality, lowered dissolved oxygen levels, increased ammonia concentration, and physiological stress symptoms in the juvenile. The decline in water quality and accumulation of metabolic waste at high densities contributed to increased stress and mortality. Besides the biological aspects, the business analysis indicated that a stocking density of 167 fish per liter was optimal in terms of economic efficiency, generating a net profit of IDR 21.467 and an R/C ratio of 1,09, making this scenario commercially viable. This study offers valuable recommendations for the sustainable management of Asian Redtail catfish juvenile transportation, promoting increased production and profitability in aquaculture. Keywords: Asian Redtail Catfish; Juvenile Transport; Profitability; Stocking Density; Survival Rate